Persistent inflammatory activation in people living with HIV. Involvement in atherosclerosis - Francisco Illanes-Álvarez; Francisco Illanes-Álvarez; Francisco Illanes-Álvarez; Denisse Márquez-Ruiz; Denisse Márquez-Ruiz; Denisse Márquez-Ruiz; Sara Cuesta-Sancho; Sara Cuesta-Sancho; Sara Cuesta-Sancho; Irene Campaña-Gómez; Irene Campaña-Gómez; Andrés Martín-Aspas; et al. (Frontiers in Medicine)
BackgroundAn increased prevalence of atherosclerosis has been observed in people living with HIV (PLWH). This study aimed to analyze levels of inflammatory, immune, endothelial, platelet, and coagulation parameters, as well as their relationship with subclinical atherosclerosis.MethodsA total of 120 PLWH with chronic infection and undetectable HIV load, along with 30 age- and sex-matched controls (HIV-uninfected individuals), were selected. Serum levels of proinflammatory molecules, including interleukin 6 (IL-6), soluble CD163, and high-sensitivity C-reactive protein, were measured. Additionally, neutrophil extracellular traps (NET)-derived parameters (anti-nucleosome antibody titers and myeloperoxidase concentrations), activated T lymphocytes, endothelial (E-selectin, vascular cell adhesion molecule 1), platelet (P-selectin, Platelet factor 4) and coagulation (D-dimer) markers were assessed. Cardiovascular risk factors were evaluated using the REGICOR and ASCVD risk estimators. In a subset of 61 individuals (18 controls and 43 PLWH), subclinical atherosclerosis was assessed by carotid Doppler ultrasound.ResultsLevels of IL-6, sCD163, anti-nucleosome antibodies, and activated T lymphocytes were elevated in PLWH compared to controls. Likewise, serum levels of platelet factor 4 and D-dimer were higher in PLWH. Those PLWH with carotid atherosclerotic lesions exhibited higher REGICOR and ASCVD scores, as well as elevated IL-6 concentrations, compared to those PLWH without carotid atherosclerotic lesions. Multivariable analysis identified the REGICOR score and IL-6 serum levels as independent factors associated with atherosclerosis.ConclusionPeople living with HIV with long-term viral load control exhibit increased levels of inflammatory, immune, platelet and coagulation markers. Subclinical atherosclerosis in this population is independently influenced by both classic cardiovascular risk factors and inflammatory activation.